2019
DOI: 10.1371/journal.pone.0221412
|View full text |Cite
|
Sign up to set email alerts
|

Curricula for empathy and compassion training in medical education: A systematic review

Abstract: Background Empathy and compassion are vital components of health care quality; however, physicians frequently miss opportunities for empathy and compassion in patient care. Despite evidence that empathy and compassion training can be effective, the specific behaviors that should be taught remain unclear. We synthesized the biomedical literature on empathy and compassion training in medical education to find the specific curricula components (skills and behaviors) demonstrated to be effective. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
135
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(169 citation statements)
references
References 96 publications
0
135
0
7
Order By: Relevance
“…In two recent systematic reviews of interventions to cultivate physician empathy, Kelm et al [1]. selected 64 studies that quantitatively assessed changes in empathy, and Patel et al [11] selected 52 studies that were controlled. More than half have been directed toward residents or physicians, that is professionals advanced in their medical training and already engaged in a specialty, which may be considered as relatively late in the curriculum [1,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two recent systematic reviews of interventions to cultivate physician empathy, Kelm et al [1]. selected 64 studies that quantitatively assessed changes in empathy, and Patel et al [11] selected 52 studies that were controlled. More than half have been directed toward residents or physicians, that is professionals advanced in their medical training and already engaged in a specialty, which may be considered as relatively late in the curriculum [1,11].…”
Section: Introductionmentioning
confidence: 99%
“…selected 64 studies that quantitatively assessed changes in empathy, and Patel et al [11] selected 52 studies that were controlled. More than half have been directed toward residents or physicians, that is professionals advanced in their medical training and already engaged in a specialty, which may be considered as relatively late in the curriculum [1,11]. The sample size was 11 to 439 subjects (median 78), the interventions lasted 40 min to 96 h (median 12 h), and 42 studies (66%) reported a significant increase in empathy [1].…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32] Thereafter, medical schools should incorporate and emphasize the curriculum including hidden ones to improve empathy and other professional expertise. 33,34…”
Section: Editorial: Empathy Among Medical Students Is An Essential Rementioning
confidence: 99%
“…The broader area of empathy or compassion training for medical trainees and physicians has found that these individuals can learn specific behaviors (such as sitting down when talking to patients or offering supportive verbal statements) that improve ratings of their degree of empathy or compassion. 2 More narrowly, regarding how to talk with patients with serious illness, the VitalTalk curriculum, typically delivered as a multisession program, has been shown to enhance the communication skills and increase the frequency of empathetic behaviors of participants. 3,4 And even more specifically, regarding how a clinician should communicate and behave when providing care to a dying child, educators have developed an interdisciplinary simulation for trainees and clinical staff to learn ways to appropriately and compassionately manage such situations.…”
mentioning
confidence: 99%
“…5 However, in terms of improving how patients or parents perceive clinicians' intentions and behaviors, doubt exists as to whether these educational efforts actually work because studies are either lacking, limited, or negative. 2,6 Not only is the literature insufficient to know what works, we clinicians also need to be wary of assuming that our self-assessment of how well we express empathy correlates with how patients (or parents) perceive us, because it does not correlate. 7 And the notion that if we employ the skill of "perspective taking" and take someone else's perspective we will be able to figure out what they want is also not backed up by evidence; it is far better to ask what someone wants than to try to guess.…”
mentioning
confidence: 99%